Teleworking and Employee Performance of Teaching Hospitals in Anambra State - Chidinma Martha Dimgba; Peter Danladi Ampa; Obera Victoria Ahonya (Britain International for Academic Research (BIAR) Publisher, 2025)
Health sectors are always faced with the responsibility of rendering good services to patients in the hospital so as to boost organizational performance. The broad objective of the study is to determine the type of relationship that exists between Teleworking and Employee performance of teaching Hospitals in Anambra State. Finding the relationship between routine teleworking and se rvice delivery of teaching hospitals in Anambra State and the relationship between situational teleworking and employee performance of teaching hospitals in Anambra state. The work was anchored on Social Exchange Theory. The population of the study is 55 workers and Pearson Moment Correlation Co-efficient was used to analyze the data. The finding showed that there is a significant relationship between routine teleworking and service delivery of teaching hospitals in Anambra state (Cal.r917>Crit.r304) and there is a significant relationship between situational teleworking and employee performance of teaching hospitals in Anambra state (Cal.867>Critr.304). The study recommends that The management of the teaching hospitals should ensure that they maintain status quo on teleworking to enjoy more efficiency from their staff. The organizations should encourage the casual employees to further trainings to incorporate better to the scheme and general innovativeness in health matters so as to update their consciousness to performance enhancement in the teaching hospitals in Anambra state.